Development of Biocompatible Ciprofloxacin-Gold Nanoparticle Coated Sutures for Surgical Site Infections - Sunitha Sampathi; Pankaj Kumar Tiriya; Sujatha Dodoala; Vijayabhaskarreddy Junnuthula; Sathish Dyawanapelly (MDPI AG, 2022)
Surgical site infections (SSIs) are mainly observed after surgeries that use biomaterials. The aim of this present work was to develop ciprofloxacin hydrochloride (CPH)-loaded gold nanoparticles. These ciprofloxacin-gold nanoparticles were coated onto a sterile surgical suture using an adsorption technique, followed by rigidization via ionotropic crosslinking using sodium alginate. Furthermore, UV-visible spectroscopy, infrared spectroscopy, and scanning electron microscopy were used to characterize the samples. The particle size of the nanoparticles was 126.2 ± 13.35 nm with a polydispersity index of 0.134 ± 0.03, indicating nanosize formation with a monodispersed system. As per the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines, stability studies were performed for 30 days under the following conditions: 2-8 °C, 25 ± 2 °C/60 ± 5% RH, and 40 ± 2 °C/75 ± 5% RH. For both Gram-negative and Gram-positive bacteria, the drug-coupled nanoparticle-laden sutures showed a twofold higher zone of inhibition compared with plain drug-coated sutures. In vitro drug release studies showed a prolonged release of up to 180 h. Hemolysis and histopathology studies displayed these sutures' acceptable biocompatibility with the healing of tissue in Albino Swiss mice. The results depict that the use of antibiotic-coated sutures for preventing surgical site infection for a long duration could be a viable clinical option.